Sexually dimorphic tibia shape is linked to natural osteoarthritis in STR/Ort mice. Issue 6 (June 2018) - Javaheri, B.; Razi, H.; Piles, M.; de Souza, R.; Chang, Y.-M.; Maric-Mur, I.; Hopkinson, M.; Lee, P.D.; Pitsillides, A.A.
Summary: Objectives: Human osteoarthritis (OA) is detected only at late stages. Male STR/Ort mice develop knee OA spontaneously with known longitudinal trajectory, offering scope to identify OA predisposing factors. We exploit the lack of overt OA in female STR/Ort and in both sexes of parental, control CBA mice to explore whether early divergence in tibial bone mass or shape are linked to emergent OA. Method: We undertook detailed micro-CT comparisons of trabecular and cortical bone, multiple structural/architectural parameters and finite element modelling (FEM) of the tibia from male and female STR/Ort and CBA mice at 8–10 (pre-OA), 18–20 (OA onset) and 40 + weeks (advanced OA) of age. Results: We found higher trabecular bone mass in female STR/Ort than in either OA-prone male STR/Ort or non-prone CBA mice. Cortical bone, as expected, showed greater cross-sectional area in male than female CBA, which surprisingly was reversed in STR/Ort mice. STR/Ort also exhibited higher cortical bone mass than CBA mice. Our analyses revealed similar tibial ellipticity, yet greater predicted resistance to torsion in male than female CBA mice. In contrast, male STR/Ort exhibited greater ellipticity than both female STR/Ort and CBA mice at specific cortical sites. Longitudinal analysis revealed greater tibia curvature and shape deviations in male STR/Ort mice that coincided with onset and were more pronounced in late OA. Conclusion: Generalised higher bone mass in STR/Ort mice is more marked in non OA-prone females, but pre-OA divergence in bone shape is restricted to male STR/Ort mice in which OA develops spontaneously.